Comparison of Turbulence Methods for a Stepped Spillway Using Computational Fluid Dynamics - Yalcin, Eyyup Ensar; Ikinciogullari, Erdinc; Kaya, Nihat (Springer Int Publ Ag, 2023)
The computational fluid dynamics (CFD) method is used effectively in hydraulic engineering and many other sciences. However, determining which turbulence model is suitable for the analysis requires further investigation. This study aims to show which turbulence method is closer to the actual data in calculating parameters, such as velocity, water surface profile, and pressure, frequently encountered in CFD engineering. For this purpose, the discharge-water level, pressure, energy dissipation rate, and velocity profile were investigated using different turbulence models (k-epsilon, k-omega, large eddy simulation [LES], renormalization group [RNG]). Then the results were compared with the physical results of stepped spillways. According to the results, the most compatible turbulence model in the discharge-water level relationship is k-omega; the most compatible turbulence model is k-epsilon for pressure, energy dissipation rates, and approach channel velocities; and lastly, the most compatible turbulence model was LES for water surface profiles. The results obtained are expected to be a reference for researchers who will work in this field.
Keywords: Stepped spillway; Flow3D; Gokceler Dam; Turbulence models